Features professional mobility in the structure of social worker - Daria Bybich (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
In the article the picture of professional mobility of social workers is given, the basic going is analysed near determination of essence of concept "mobility", to realize ability able the necessity, to pass from one level of professional activity to other, extending and deepening the level of this activity, showing the professional competence.
Keywords: professional mobility; social worker; competence; components; approaches; jurisdictions